Ultrasounds pretreatment of olive pomace to improve xylanase and cellulase production by solid-state fermentation - Leite, A. (2016)
Abstract Olive mills generate a large amount of waste that can be revaluated. This work aim to improve the production lignocellulolytic enzymes by solid-state fermentation using ultrasounds pretreated olive mill wastes. The composition of olive mill wastes (crude and exhausted olive pomace) was compared and several physicochemical characteristics were significantly different. The use of both wastes in SSF was evaluated and a screening of fungi for xylanase and cellulase production was carried out. After screening, the use of exhausted olive pomace and A. niger led to the highest enzyme activities, so that they were used in the study of ultrasounds pre-treatment. The results showed that the sonication led to a 3-fold increase of xylanase activity and a decrease of cellulase activity. Moreover, the liquid fraction obtained from ultrasounds treatment was used to adjust the moisture of solid and a positive effect of xylanase (3.6-fold increase) and cellulase (1.2-fold increase) production was obtained.